High-frequency migraine refractory to usual pharmacological treatment and antibody and responsive to full-spectrum cannabidiol: a case report - Rosa, Lia Mara Mesquita; Araújo Siega, Márcio Rafael de (Headache Medicine, 2022)
The use of derivatives of Cannabis sp. in the treatment of certain medical conditions, such as neuropathic pain, epilepsy and multiple sclerosis, is well known. However, studies on its benefit in headache are low in scope, consisting, in majority, of reports and case series. We report the case of a 74-year-old male patient with high frequency migraine (2 to 3 times/week) for several years, presenting important functional limitation associated with several triggers, and using triptans for headache crisis only. The patient expressed intolerance to 2 prophylactic drugs (topiramate and propranolol). He performed 2 applications of Erenumab 70 mg, wich promoted considerable initial improvement followed by a new increase in attacks’ frequency after the second application, leading to interruption of this therapy. Nutraceuticals were tried for 6 months, but there was not any improvement. After the introduction of cannabidiol oil, migraine attacks reduced in frequency (1 episode/month) and intensity, with a record interval of 30 consecutive days without pain, associated with elimination of triggers. Preclinical studies evaluating the relationship between endocannabinoid system and migraine pathophysiology point to Cannabis sp. derivatives as potential weapons for the treatment of this condition. However, the role of these derivatives as prophylaxis of migraine attacks is still speculative, thus requiring controlled studies for further definition.